Influence of Physical Activity during Pregnancy on Neonatal Complications: Systematic Review and Meta-Analysis - Silva-Jose, Cristina; May, Linda; Sánchez Polán, Miguel; Zhang, Dingfeng; Barrera Garcimartín, Alejandro; Refoyo, Ignacio; Barakat, Rubén (My University, 2023)
.

Newborn hospitalisations after delivery are indicators of poor neonatal health with potential risks of future diseases for children. Interventions to promote a healthy environment have been used during pregnancy, with physical activity as a principal element. A systematic review and meta-analyses were performed to evaluate the effect of physical activity during pregnancy on neonatal intensive care unit (NICU) admissions and Apgar 1 and 5 scores (Registration No.: CRD42022372493). Fifty studies (11,492 pregnant women) were included. There were significantly different rates of NICU admissions between groups (RR = 0.76, 95% CI = 0.62, 0.93; Z = 2.65, p = 0.008; I2 = 0%, and Pheterogeneity = 0.78), and significant differences in Apgar 1 (Z = 2.04; p = 0.04) (MD = 0.08, 95% CI = 0.00, 0.17, I2 = 65%, Pheterogeneity = 0.00001) and Apgar 5 (Z = 3.15; p = 0.002) (MD = 0.09, 95% CI = 0.04, 0.15, I2 = 80%, and Pheterogeneity = 0.00001), favouring intervention groups. Physical activity during pregnancy could help to reduce the risk of NICU admissions that are related to neonatal complications.
Artículos en revistas